Neutrophil gelatinase-associated lipocalin as a predictor of treatment outcomes in primary glomerulonephritis - Stražmešter Majstorović, Gordana; Mitić, Igor; Djurović, Vladimir; Golubović, Sonja; Petrović, Lada; Knežević, Violeta (Vojnosanitetski pregled, 2026)
Background/Aim. Biomarkers for predicting disease course could facilitate treatment selection in primary glomerulonephritis (PGN). Data on the role of neutrophil gelatinase-associated lipocalin (NGAL) in PGN are limited. The aim of this study was to evaluate the significance of NGAL in predicting treatment outcomes in PGN. Methods. The study included a total of 60 PGN patients followed between 2012 and 2024. At diagnosis, serum NGAL (sNGAL) and urinary NGAL (uNGAL) were measured. Renal function parameters (serum creatinine, proteinuria) and disease outcome–development of end-stage renal disease (ESRD)–were assessed at baseline, after 5 years, and at the end of the follow-up period. The association between NGAL and clinical outcomes was analyzed using appropriate statistical tests. Results. At baseline, median sNGAL and uNGAL levels were 154.71 ng/mL and 13.94 ng/mL, respectively. During a median follow-up of 112 months, 8.33% of patients were lost to follow-up, and 20% developed ESRD. Patients who developed ESRD had higher sNGAL levels (p = 0.027). Using sNGAL, ESRD was fairly predictive (AUC = 0.709; p = 0.036), and sNGAL was associated with time-to-ESRD (Kaplan-Meier analysis, p < 0.001). The group with the highest sNGAL showed the lowest 5-year renal survival. Patients with stable or improved estimated glomerular filtration rate (eGFR) had higher uNGAL/creatinine ratio values (p = 0.049). Changes in proteinuria correlated negatively with sNGAL (p < 0.001) and uNGAL (p = 0.005). Conclusion. In PGN, sNGAL could be a predictor of ESRD development, potentially reflecting its pro-fibrotic activity. In contrast, the correlation between NGAL levels and change in proteinuria, as well as the associations between higher uNGAL/creatinine ratios and improved eGFR, suggest a complex and potentially protective role of NGAL in disease progression.